(untitled) (Journal of the Bangladesh Agricultural University, 2024)
In the present study, the effect of some reduced risk insecticides was evaluated against sucking insect complex on okra. The selected reduced risk insecticides were Biotrin 0.5% (Matrine 0.5%), Capture 75 WDG (Imidacloprid + Emamectin Benzoate), Kotan 50 WG (Pymetrozine), Ravjum 14.5 SC (Indoxacarb) and Sniper 10 SC (Fenopropathrin + Fenvalerate). A total of four sprays were given at 10 days interval. Data were collected on the number of insects/leaf, number of curled leaves per plant and marketable yield of okra (t/ha). Considering the reduction of jassid populations, the best result was found in case of Kotan 50 WG (0.51 jassid/leaf after given 4th spray) and Sniper 10 SC (0.67 jassid/leaf after given 4th spray) treated plots while the next best treatments were Capture 75 WDG (1.0 jassid/leaf) and Ravjum 14.5 SC (1.56 jassid/leaf) respectively. But Biotrin 0.5% was found ineffective or less effective against sucker complex of okra (8.0 jassid/leaf) and this result was comparable with untreated control (10.25 jassid/leaf). A similar trend was found in case of whitefly and aphid populations following given treatments. Numbers of curled leaves were significantly reduced in insecticides treated plots except Biotrin 0.5%. The highest marketable fruit yield (10.56t/ha) was found from Kotan 50 WG treated plots @ 1.0 g/L that was insignificantly followed by Sniper 10 SC @ 1.5 ml/L (10.44 t/ha). The lowest yield was recorded from control plots (6.12 t/ha) and the plots treated with Biotrin 0.5% (6.50 t/ha). J Bangladesh Agril Univ 18(3): 578–584, 2020 https://doi.org/10.5455/JBAU.3626